The praxis in training of Community Psychology: An ethical view - Rivera Holguín, Miryam (2018)
The aim of this study was to explore the praxis in training of Community Psychology and identify the characteristics of the role and ethical work. This was done by analyzing the syllabi of Community Psychology courses in Psychology programs in Peru that include those courses in their plan of studies. The study seeks to analyze the extent of supervision of practical work that is included as a substantial part of the training. The results show that 16 of the 20 syllabi of the courses offered by the analyzed universities included theoretical and practical training, but that only one course explicitly offers a space for accompaniment, supervision and / or monitoring. In addition, there is only reflection on one’s attitude toward the role and community involvement, and not critical reflection. Thus, the ethical and political dimension of training in Community Psychology is absent.